2015
DOI: 10.1002/sej.1204
|View full text |Cite
|
Sign up to set email alerts
|

Toward An Integration of the Behavioral and Cognitive Influences on the Entrepreneurship Process

Abstract: Research summary: Entrepreneurs develop innovations, fulfill customer needs, and spur economic growth by recognizing, evaluating, and exploiting opportunities. Despite progress, scholarly understanding of how entrepreneurs achieve these objectives may be incomplete. For instance, little explanation exists for why entrepreneurs may pursue activities seemingly at random, nor is there a clear endpoint to the entrepreneurship process. To address these concerns, we present a framework that integrates sensemaking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 138 publications
1
53
0
5
Order By: Relevance
“…Past research has demonstrated some differences in the effectiveness of self-regulatory strategies across different phases of the entrepreneurial process, and different levels of entrepreneurial experience. For example, Pryor, Webb, Ireland and Ketchen (2016) hypothesized that novice and experienced entrepreneurs would develop different behavioral scripts with regard to opportunity recognition, evaluation and exploitation.…”
Section: Self-regulation In Entrepreneurs 33mentioning
confidence: 99%
“…Past research has demonstrated some differences in the effectiveness of self-regulatory strategies across different phases of the entrepreneurial process, and different levels of entrepreneurial experience. For example, Pryor, Webb, Ireland and Ketchen (2016) hypothesized that novice and experienced entrepreneurs would develop different behavioral scripts with regard to opportunity recognition, evaluation and exploitation.…”
Section: Self-regulation In Entrepreneurs 33mentioning
confidence: 99%
“…Workplace relationships can offer mentoring, shape preferences and allow employees to flourish (Colbert et al, 2016), and also legitimize opportunities identified through experience, observation, and communication (Nanda & Sørensen, 2010;Pryor et al, 2016). Employees' satisfaction, performance, retention, and mobility are found to be molded by others at work, most often hierarchical superiors with more authority, seniority, and experience (Abraham, 2017;Artz et al, 2017;Artz & Taengnoi, 2016;Lazear et al, 2015;McGinn & Milkman, 2013), sometimes perceived as role models (Gibson, 2004).…”
Section: Individual Heterogeneous Preferences and The Value Of Mentmentioning
confidence: 99%
“…Finally, having access to mentoring from role models can have a particularly strong impact for individuals not yet exposed to (in)direct entrepreneurial career previews which could have changed their beliefs about or preferences for entrepreneurship (Greenberg, 2014;Lentz & Laband, 1990;Lyons & Zhang, 2018;Tonoyan et al, 2019). We expect the existence of such gaps to leave more room for role models to provide information and create awareness of the different phases involved in entrepreneurship (Pryor et al, 2016). We therefore hypothesize that:…”
Section: Heterogeneities In Female Founders' Social Influencementioning
confidence: 99%
See 1 more Smart Citation
“…Mental models reflect individuals' cognitive frameworks that define plausibility, effectiveness, or some other form of acceptability (Pryor et al, 2015). In this study, we look at the emergence of market-oriented mental models which reflect sensemaking processes regarding problem solving for (superior) customer value creation.…”
mentioning
confidence: 99%